Implementation of a brief training programme to reduce mask leak with a respiratory function monitor - Neaha Patel; Burak Salgin; Ludovic Chassin (BMJ Paediatrics Open)
Respiratory function monitors (RFMs) can provide real-time data including expiratory tidal volumes and interface leak during delivery room (DR) neonatal resuscitation. However, concerns have been raised within previous randomised controlled trials and systematic reviews that effectuating RFMs routinely for DR resuscitation is limited by lack of comprehensive staff training. The International Liaison Committee on Resuscitation have also recently declared a knowledge gap in terms of the training required to be competent in utilising an RFM during neonatal resuscitation. We conducted an experiment with thirteen medical students who had no prior resuscitation experience to see if visual feedback from an RFM could improve mask leak when ventilating an extremely preterm manikin. Following a brief training session with hands-on practice, 260 breaths were analysed and median mask leak improved from 45% (IQR 25-62%) during the first breath to 0% (IQR 0-1%) by the twentieth and final breath. The median expiratory tidal volume was 3.6 mL (IQR 3.4-3.8 mL) and remained stable. This manikin experiment has demonstrated that even a short and experiential training session with an RFM for participants with no prior resuscitation training can be effective in reducing mask leak.